Lady oracle and mass literature: female stereotypes - Eliane C. Campello; Eduardo F. Souza (Ilha do Desterro)
Lady Oracle 1 (1976) is a metafictional2 novel, narrated from the perspective of a woman writer who interweaves the story of her lifewith excerpts from the books she writes, pieces of criticism on them and commentaries on the act of writing. The novel is built on intermingled and juxtaposed narrative levels. The main narrative course that tells the story of the writer Joan Foster is broken, now and then, to give room to the stories she writes, such as Stalked by Love, which is totally reproduced, and The Lord of Chesney Chase, Love, My Ransom, Escape for Love, and Lady Oracle (a book of poems), which we know of through references or fragments